MiR-223-3p Alleviates Vascular Endothelial Injury by Targeting IL6ST in Kawasaki Disease - Xiang Wang; Xiang Wang; Yue yue Ding; Ye Chen; Qiu qin Xu; Guang hui Qian; Guang hui Qian; Wei guo Qian; Lei Cao; Wan ping Zhou; Miao Hou; Hai tao Lv (Frontiers Media S.A., 2019)
Background: Kawasaki disease (KD) is a self-limiting illness with acute systematic vascular inflammation. It causes pathological changes in mostly medium and small-sized arteries, especially the arteria coronaria, which adds the risk of developing coronary heart disease in adults.Materials and methods: We detected the miR-223-3p expression in 30 KD patients combined with 12 normal controls using miRNA microarrays and RT-PCR. A KD mouse model was constructed using Candida albicans water insoluble substance (CAWS). We also checked the miR-223-3p's expression using qRT-PCR. The Luciferase reporting system was implemented to validate the correlation between miR-223-3p and Interleukin-6 receptor subunit beta (IL-6ST). TNF-α was used to stimulate human coronary artery endothelial cells (HCAECs), and miR-223-3p activator or inhibitor and KD serum were used to treat HCAECs. A Western blotting automatic quantitative analysis protein imprinting system was used to test the expression of signal transducer and the activator of transcription 3 (STAT3), phosphorylated-signal transducer and the activator of transcription 3 (pSTAT3) and NF-κB p65.Results: Clinical trials found that miR-223-3p expressions were markedly different (more than 2-fold) between the acute KD group and the control group. E-selectin and intercellular cell adhesion molecule-1 (ICAM-1) levels were also significantly higher (about 2-fold) in KD especially with coronary artery lesions. MiR-223-3p could alleviate vascular endothelial damage in KD mice, and IL-6 (Interleukin-6), E-selectin and ICAM-1 were simultaneously negative. The values of IL-6, E-selectin, and ICAM-1 mRNA expressions decreased, while the value of IL-6ST was increased between the agonist treated mice and KD mice. The RT-qPCR consequences displayed that miR-223-3p explored the highest expression on the third day in both the KD mice as well as the agonist group. MiR-223-3p can directly combine with IL-6ST 3' untranslatable regions (UTR) and held back the IL-6's expression. Overexpression of miR-223 down regulated IL6ST expression and decreased the expression of p-STAT3 and NF-κB p65, while the miR-223 inhibitor could reverse the above process.Conclusion: MiR-223-3p is an important regulatory factor of vascular endothelial damage in KD and could possibly become a potential target of KD treatment in the future.